Metabolic Control of Treg Cell Stability, Plasticity, and Tissue-Specific Heterogeneity - Shi, Hao; Chi, Hongbo (Frontiers in Immunology, 2019)
Regulatory T (Treg) cells are crucial for peripheral immune tolerance and prevention of autoimmunity and tissue damage. Treg cells are inherently defined by the expression of the transcription factor Foxp3, which enforces lineage development and immune suppressive function of these cells. Under various conditions as observed in autoimmunity, cancer and non-lymphoid tissues, a proportion of Treg cells respond to specific environmental signals and display altered stability, plasticity and tissue-specific heterogeneity, which further shape their context-dependent suppressive functions. Recent studies have revealed that metabolic programs play pivotal roles in controlling these processes in Treg cells, thereby considerably expanding our understanding of Treg cell biology. Here we summarize these recent advances that highlight how cell-extrinsic factors, such as nutrients, vitamins and metabolites, and cell-intrinsic metabolic programs, orchestrate Treg cell stability, plasticity and tissue-specific heterogeneity. Future exploration of immunometabolism of Treg cells should provide new insight into immune homeostasis and disease, with important therapeutic implications for autoimmunity, cancer and other immune-mediated disorders.